Pendidikan Karakter dalam Keluarga Perspektif Al-Quran - Dede Sutisna; Hasanah, Aan; Arifin, Bambang Samsul (Jurnal Indragiri Penelitian Multidisiplin, 2025)
Character education in the family is the main foundation in the formation of ethical and moral individuals. This research aims to explore the concept of character education based on an Al-Quran perspective in the family environment. The method used is library research, by collecting data from various relevant primary and secondary literature sources. The research results show that family character education has main components, namely objectives, programs, processes and evaluation. Based on the Koran, the goals of character education include protecting the family from the torment of hell, forming noble morals, and creating individuals who are strong spiritually, socially and professionally. Educational programs include example, habituation, advice, motivation and punishment. The educational process relies on the curriculum and applicable methods such as example and habituation. Evaluation is carried out through continuous observation of children's performance. This research confirms that the family has a vital role in forming a generation with strong character, in line with the guidance of the Koran, in order to create a society with noble morals. This research also identifies stages of character education starting from pre-marriage to childhood and adolescence, with an approach based on Islamic values, such as prayer, moral education and example.